JOHN F. WANSBROUGH DAN SALVATION HISTORY DALAM KAJIAN ISLAM - Akh. Minhaji (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
The most important vision and mision of education is not to teach students “what to think” but rather “how to think.” By doing so, students hopefully be able to think historically. This will encourage the students to use his mind critically as well as scientifically so that they are able to distinguish sharply, for example, (1) “religious truth claim,” (2) “intellectual truth claim,” (3) “ultimate truth;” and also between “religious understanding of history” and “historical understanding of religion.” The present essay argues that the positive way of thinking mentioned above was (is) not working properly in UIN, even in PTAIN/S in general. By referring to the idea of Fazlur Rahman (normative and historical Islam) and also A. Mukti Ali (scientific-cum-doctrinaire), Prof. Simuh indicated the problem in his quite a number of works. Realizing the fact, it is our academic responsibility to understand critically the situation and (then) to contribute significantly through any effort so that our academic vision, mission, and tradition becomes better. As an introduction to the problem and as an initial effort to anticipate such a problem, the following article presents the idea of John F. Wansbrough on “Salvation History,” hoping that the problem will be understood properly and analyzed more deeply and critically